Examining Trauma Cognitions as a Mechanism of the BRITE Intervention for Female-Identifying Individuals with PTSD Symptoms and Alcohol Misuse - Elizabeth A. Lehinger; Molly Joseph; Antoine Lebeaut; Scott Graupensperger; Debra Kaysen; Michele A. Bedard-Gilligan (Behavioral Sciences)
Trauma cognitions have been widely supported as a mechanism of change in post-traumatic stress disorder (PTSD) treatment. Less is known about the mediating role of trauma cognitions in early interventions addressing PTSD symptoms and co-occurring conditions such as alcohol misuse. This study was a secondary analysis of data collected as part of a pilot randomized clinical trial of a single session intervention and four coaching calls (BRITE), adapted from Cognitive Processing Therapy for survivors of a sexual assault that occurred in the past 10 weeks. Fifty-seven adult female-identifying individuals with symptoms of PTSD and alcohol misuse randomized to either intervention or symptom monitoring completed the assessments of PTSD severity, alcohol use, and trauma cognitions at intake, post-intervention, and 3-month follow-up. Mixed-effects models showed trauma cognitions improved significantly in the BRITE condition but did not change in the symptom monitoring condition (b = −1.53, p < 0.001, B = −1.05). Mediation analyses indicated that change in total trauma cognitions and self-blame cognitions did not have a significant indirect effect on the association between condition and PTSD symptoms and average drinks on drinking days, and the proportion mediated was small for PTSD symptoms and average drinks. Preliminary findings indicate reductions in negative trauma cognitions for the BRITE condition, but this is likely one of several factors that play a role in changes in PTSD symptoms and alcohol use in the early recovery period following sexual assault.